ANALISIS TINGKAT KEPUASAN DAN PARTISIPASI ANGGOTA KOPERASI PRODUKSI TERNAK MAJU SEJAHTERA - Dewa Ayu Puspa Aprillya; Dyah Aring Hepiana Lestari; Agus Hudoyo (Journal of Food System & Agribusiness, 2022)
The research aimed to measure the rate of cooperative members’ satisfaction on the cooperative service, to determine the rate of members’ participation in the annual member meeting, payment of obligatory savings, and the use of business service as well as to analyze the factors influencing the member participation in the annual member meeting and the use of business service. The research method was a survey. The data were analysed through method of CSI (Customer Satisfaction Index), descriptive quantitative analysis, and logistic regression. The number of samples was 53 cooperative members. The research found that the rate of cooperative members’ satisfaction fell into very satisfied category, the rate of participation in the annual member meeting was categorized into low category, the rate of participation in paying the obligatory savings was categorized into high category, the rate of participation in utilizing the business service was categorized into low category. The factors influencing the rate of cooperative members’ participation in the annual member meeting and utilizing the business service were the family members and non-formal education.